Are Mocha, Thinking Pinoy really fake news?. IN Sisyphus' Lament [column] - Tan, Oscar Franklin (Philippine Daily Inquirer, 2017)
The article presents the argument whether we should really consider the likes of nonjournalists like Mocha Uson and RJ Nieto of "Thinking Pinoy" for every casual mistake or misunderstanding on their online portals such as Facebook.